EVALUATION OF THE FUNCTIONAL PROBABILITIES OF THE BLOOD PLASMA TRANSPORT SYSTEMS OF THE LIVER CIRRHOSIS PATIENTS BY THE FLUORESCENT PROBES METHOD AND ASSESSING OF HYDROPHOBIC SUBSTANCES ELIMINATION AFTER HEMOSORPTION AT THESE PATIENTS - E. V. Korolik; A. A. Ivanov; N. I. Insarova; V. G. Leshenko; F. I. Kazakov; A. K. Korolik; V. V. Kirkovskii (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of investigation of the main blood plasma transport proteins binding ability at liver cirrhosis patients by the fluorescent probes method are presented. It is shown that fluorescent probes method allows to get express information about functional state of the main blood plasma transport proteins at liver cirrhosis patients, promptly assess the disease severity, and according to this information change their treatment quickly.